Safety and efficacy of recombinant activated factor VII for refractory hemorrhage in pediatric patients on extracorporeal membrane oxygenation: a single center review. (March 2014) - Long, MT; Wagner, D; Maslach-Hubbard, A; Pasko, DA; Baldridge, P; Annich, GM
Background: Medically refractory hemorrhage in patients on ECMO (extracorporeal membrane oxygenation) support can have catastrophic complications. Recombinant-Activated Factor VII (rFVIIa; NovoSeven®) may provide lifesaving hemostasis; however, there are reports of catastrophic thrombosis related to its administration. Objective: This review attempts to add safety and efficacy data to existing literature regarding the use of rFVIIa for refractory hemorrhage in pediatric patients on ECMO support. Design/Methods: A retrospective chart review was performed for all pediatric patients on ECMO who received rFVIIa for refractory hemorrhage from 2004 to 2009. Data was extracted for each refractory bleeding event, including patient blood loss and transfused blood products in the 6 hours before the first dose, between rFVIIa doses and in the 6 hours after the final dose. For purposes of data collection, a hemorrhagic event was defined as new onset hemorrhage or a hemorrhage occurring at least 12 hours after the most recent dose of rFVIIa. Results: In total, seven patients aged 1 month to 15 years received rFVIIa for 14 different hemorrhagic events. There was no significant difference in blood loss or blood product transfusion associated with rFVIIa administration. There was one patient-related and one ECMO-related complication temporally associated with rFVIIa administration: decreased ECMO circuit oxygenator efficiency and the development of an intra-gastric clot requiring surgical evacuation. Conclusion: These data suggest limited efficacy for rFVIIa use for refractory hemorrhage in pediatric patients on ECMO support. There were two non-catastrophic complications temporally associated with its administration.